Pengaruh Stretching Exercise terhadap Keluhan Musculoskeletal Disorder pada Pengrajin Sulam Usus di Desa Margodadi, Kecamatan Jati Agung, Kabupaten Lampung Selatan - Gunata, Agustina Fadilla; Mayasari, Diana (Medula, 2024)
Sulam usus is a distinctive fashion of Lampung, made by sateen, which manufactured manually by hands. This process requiring meticulous detail, that lead to neck flexion and trunk bend posture, which can cause musculoskeletal disorder symptoms. One of the conservative therapy of musculoskeletal disorder is stretching exercise. This study aims to determine the effect of stretching exercise on musculoskeletal disorder symptoms among sulam usus worker in margodadi subdistrict jati agung district lampung selatan regency. This research used quasi experimental method with pre-posttest one group design, involving 28 respondents. Respondents will be given treatment of stretching exercise as much as 2 times daily for four weeks. The first and second score of musculoskeletal symptoms measured using a nordic body maps questionnaire. Data were analyzed by paired- samples t test with α = 0.05. In this study there was a significant difference of musculoskeletal disorder score mean different between the first score dan the second score (p=0,000). There is an effect of stretching exercise on musculoskeletal disorder symptoms among sulam usus worker in Margodadi Subdistrict Jati Agung District Lampung Selatan Regency.